Corelation between Preoperative Serum CEA, CA19-9, and AFP Levels and Clinicopathologic Factors (Annals of Medical Research, 2021)
None
Keywords: Gastric Adenocarcinoma, CEA, CA19-9, AFP, Clinicopathologic Factors